The Bible in the Iglesia Filipina Independiente - Smit, Peter-Ben (2021)
The Iglesia Filipina Independiente (IF) has developed its own position regarding the interpretation of the Bible. This article charts the evolution of the IF's hermeneutical position throughout the three main phases of its historical and theological development drawing on official and representative statements made by the church and its leadership. It shows how the development of the biblical hermeneutics of the IF parallels the historical trajectory of the church at large, from its inception under the leadership of Gregorio Aglipay and Isabelo de los Reyes Sr.) to the centennial celebration of its proclamation in 2002.
Keywords: Iglesia Filipina Independiente; Catholicism